Combining Reicherts and Millards approaches in the management of unilateral labial fissure - Rossell Perry, Percy (2008)
Introduction: The anatomy of labial fissure is different for each patient, and many authors have described modifications of the traditional techniques aiming at obtaining individualized designs with less incisions and better results. Reichert-Millards technique is perhaps the surgical approach most frequently used by surgeons all over the world for the management of labial fissures; however, there are some limitations when using this method when trying to obtain an individual design of the fissure to be repaired. Consequently, some modifications for Millards approach on the basis of the Lima Outreach Center severity classification and the shape of the nasal filter were proposed. Objective: To propose a combination of Millards and Reicherts approaches based on the natural lines of the lips and the severity of the labial fissure, while trying to obtain a more individual design. Material and Method: A retrospective and descriptive study was performed in 112 patients. The technique was based in three concepts: shape, severity, and the natural lines of the lips. Incisions were made upon the natural lines of the lips, between the aesthetic subunits of the upper lip. The incision for rotating the nasal filter was designed by imitating the column of the filter from the normal side with a good aesthetic result. The modification of the forward flap was performed avoiding a subnasal incision. The results obtained with this technique were assessed considering the number of poor results by following up patients for more than one year through direct physical examination and analyzing preoperative frontal and "worms view" photographs. Results: From 2004 to 2007 this technique has been used in 112 cases of unilateral labial fissure. Good aesthetic and functional results in the nose and upper lip areas were obtained using this technique, and only 14.2% of the outcomes corresponded to poor and fair results. The latter are surgical procedures that required secondary revision. Conclusion: This is a modification of Millards approach, with good aesthetic results (lower number of incisions and a more individual design compared to traditional techniques) for the reconstruction of the upper lip and the nose in cases of unilateral labial fissure.